Understanding the mechanism of amylin aggregation: From identifying crucial segments to tracing dominant sequential events to modeling potential aggregation suppressors - Ghosh, Ritama; Ghosh, Shreyan; Das, Atanu (Biochimica Et Biophysica Acta-Proteins and Proteomics, 2023)
One of the most abundant, prevailing, and life-threatening human diseases that are currently baffling the scientific community is type 2 diabetes (T2D). The self-association of human amylin has been implicated in the pathogenesis of T2D, though with an inconclusive understanding of the mechanism. Hence, we focused on the characterization of the conformational ensembles of all the species that are believed to define the structural polymorphism of the aggregation process - the functional monomeric, the initially self-associated oligomeric, and the structured protofibril - by employing near-equilibrium, non-equilibrium, and equilibrium atomistic simulations on the sporadic, two familial variants (S20G and G33R), and their proline-substituted forms (S20P and G33P). The dynamic near-equilibrium assays hint toward - the abundance of helical conformation in the monomeric state, the retainment of the helicity in the initial self-associated oligomeric phase pointing toward the existence of the helix-helix association mechanism, the difference in preference of specific segments to have definite secondary structural features, the phase-dependent variability in the dominance of specific segments and mutation sites, and the simultaneous presence of generic and unique features among various sequences. Furthermore, the non-equilibrium pulling assays exemplify a generic sequential unzipping mechanism of the protofibrils, however, the sequence-dependent uniqueness comes from the difference in location and magnitude of the control of a specific terminus. Importantly, the equilibrium thermodynamic assays efficiently rank order the potential of aggregability among sequences and consequently suggests the probability of designing effective aggregation suppressors against sporadic and familial amylin variants incorporating proline as the mutation.
Keywords: Aggregation mechanism; Bridging information; Conformational polymorphism; Generic suppressor; Helix -driven association; Structural reorganization